ANALISIS KESEIMBANGAN DAN KOORDINASI MATA KAKI DITINJAU DARI TINGKAT KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PASSING PADA PERMAINAN FUTSAL EKSTRAKULIKULER MAN 2 KOTA MAKASSAR - Muh. Zubair; Muh. Adnan Hudain, Imam Suyurd; Benny Badaru, Arimbi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The type of research in this thesis is Path Analysis research. This study aims to determine the analysis of balance and ankle coordination in relation to the level of confidence in passing ability in the extracurricular futsal game of Man 2 Kota Makassar. The sample size for this study is 30 participants.